Defoliation management effects on nutritive value of 'performer' switchgrass. Issue 3 (20th March 2020) - Bekewe, Perejitei E.; Castillo, Miguel S.; Acosta, Juan J.; Rivera, R.
Abstract: Forage species with greater nutritive value have the potential to positively affect animal responses. 'Performer' switchgrass ( Panicum virgatum L.) was released because of greater digestibility and lower lignin concentrations as compared to 'Alamo' and 'Cave‐in‐Rock.' However, the relationship between nutritive value, canopy characteristics, and dry matter yield for this species has not yet been established. The goal of this study was to determine in vitro true digestibility (IVTD), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) as a function of a wide range of defoliation management strategies to aim optimize production of nutritious forage. Treatments were the factorial combination (4 × 4) of defoliation height (DH; clipped to 10, 20, 30, and 40 cm) and defoliation frequency (DF; clipped every 3, 6, 9, and 12 wk). The range of digestibility values was greater due to DF (from 590–779 g kg −1 when averaged across DH treatments) than DH treatments (from 675–692 g kg −1 when averaged across DF treatments). In general, frequent defoliation resulted in greater IVTD and CP but lower yields; however, there were interaction effects of DF × DH for all response variables. With the exception of NDF, all response variables had strong correlations with dry matter yield, canopy height, and leaf/stem ratio. Although there are tradeoffs when managing for productivity and nutritive value, there is a wide range of defoliation management options for 'Performer' switchgrass that provide flexibility in terms of harvesting schedules to optimize productivity and persistence of nutritious forage.